Mujer y mestizaje :Traspasando fronteras étnico-sociales en el Buenos Aires Colonial - Antonio Fuentes Barragán (Nuevo mundo - Mundos Nuevos, 2012)
In a social class structure, apparently rigid, overpowered by males, a woman, which was stigmatized as a descendant of a laundress of mixed black blood, in eighteenth century Buenos Aires climbed to the top of the social ladder through a series of methods. The purpose of this analysis is to study the scene in which our actress, Doña Petrona de Muga y Peralta, had to overcome the socio-ethnic and gender prejudices by her performance in the community.